Relationship between erectile dysfunction and alexithymia in male patients with implantable cardioverter defibrillators: a cross-sectional study - Ledermann, Katharina; Zuccarella-Hackl, Claudia; Altwegg, Rahel; Dörner, Marc; Attanasio, Veronica; Guth, Lisa; Zirngast, Sina; Pazhenkottil, Aju P.; Menzi, Anna; von Känel, Roland; Princip, Mary (Frontiers in Psychiatry, 2024)
Implantable Cardioverter-Defibrillator (ICD) implantation is a life-saving intervention for individuals at risk of life-threatening arrhythmias. However, the psychosocial impact of ICD implantation extends beyond its cardiovascular benefits, potentially influencing emotional well-being and sexual health. This can lead to erectile dysfunction, which, is often associated with alexithymia. Both erectile dysfunction and alexithymia can significantly affect the psychological well-being of both patients and their partners.Aims: This study examines the association of erectile dysfunction with alexithymia in patients after ICD implantation. Additionally, we investigate potential moderators of this association.Method: Patients (N=165) completed self-rating questionnaires: Toronto Alexithymia scale (TAS-20), International Index of Erectile Function (IIEF-5), Adjustment disorder -new module (ADNM-20). Descriptive statistics, correlations, multivariate linear regressions, and moderation analysis were conducted.The determinants of erectile dysfunction in ICD patients were explored in a regression model explaining 22 % of the total variance. The ADNM-20 subscale preoccupation was found to significantly moderate the relationship between the alexithymia subscale externally oriented thinking and erectile dysfunction (R2 =0.02, p=0.03).We did not find evidence for a relationship between externally oriented thinking and erectile dysfunction at low to average levels of preoccupation. However, evidence for such a relationship was found at high levels of preoccupation, where more externally oriented thinking was related to more erectile dysfunction. The intersection of alexithymia and erectile dysfunction represents a promising avenue for future research, offering opportunities to unravel the intricate connections between emotional processing and sexual health. Enhancing insights into this relationship could lead to innovative interventions that address the needs of individuals struggling with both conditions, fostering improved emotional expression, intimate relationships, and sexual satisfaction.